Gambaran Kondisi Ibu Hamil dengan Diabetes Mellitus di RSD dr. Soebandi Jember Tahun 2013-2017 (Description of Pregnant Women Condition with Diabetes Mellitus in RSD dr. Soebandi Jember on 2013-2017) - Meggeria Dyah Matrika Tito Putri; Pudjo Wahjudi; Irma Prasetyowati (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Abstract Diabetes Mellitus or diabetes is a chronic metabolic disease disorder caused by pancreas does not produce enough insulin or the body can’t effectively use produced insulin. In pregnant women with a family history of diabetes mellitus, the prevalence of pregnancy with diabetes mellitus is 5.1%. This research aim to determine description of pregnant women condition with diabetes mellitus in RSD dr. Soebandi Jember. This research used descriptive method with case series design. The sample size of 19 pregnant women with diabetes mellitus was selected by total sampling technique. The results showed that the high maternal age (52.6%), low education (89.5%), unemployment or housewife (89.2%), had a genetic 78.9%), BMI overweight (57.9%), glucosuria (89.5%), history of pre-eclampsia (57.9%), low parity (79%), never miscarried (84.2%). Based on the result of the research, it was concluded that maternal education, maternal job, genetic, overweight BMI, glucosuria, and history of pre-eclampsia had an effect towards the occurrence of pregnant women with diabetes mellitus, also maternal age, parity and history of miscarriage had no effect on the occurrence of pregnant women with diabetes mellitus. To raise awareness of the risks of pregnancy with diabetes mellitus can be done with screening for diabetes mellitus. Keywords: diabetes mellitus, pregnant women, RSD dr. Soebandi.